Kepoque Leko’s / Mohamad Shahril Rizal Harun ... [et al.] - Harun, Mohamad Shahril Rizal; Mahmod, Khairunnisa Naziha; Abdul Majid, Zeti Alysa; Wan Badrul Hisham, Wan Nur Afiqah; M Maamor, Nur Alysha (2021)
In this report, the name of the business for this project is Kepoque Leko’s, which sells keropok lekor, a food-based product. The one who owns and run the business was Miss Afiqah Hisham where she is also the one who manage to get the best keropok lekor supply from Terengganu. The keropok lekor are being sold with 500 grams each pack for only at RM 10.00. The price is really affordable as it is quite cheaper than the standard price. Since it is an online business, the people would browse around social medias to buy the product. Therefore, Kepoque Leko’s had created an Instagram business account as a platform used for people to perceive information about the products. Hence, the delivery services are also provided using courier services and runner services. The report contains more information in detail about Kepoque Leko’s including the business and product descriptions, the organizational, marketing plan, operation plan and financial plan. Despite all the information that had been collected, we are able to complete the whole report for the Business Plan perfectly.